#### Answer

The solution is $x = 0.5$

#### Work Step by Step

$4x^2 - 4x + 1 = (2x - 1)^2= 0$
$2x - 1= 0$
$2x = 1$
$x = 0.5$
OR
$2x - 1= 0$
$2x = 1$
$x = 0.5$
The solution is $x = 0.5$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

The solution is $x = 0.5$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.